Bioetica ambientale, sostenibilità, teoria intergenerazionale della Costituzione (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
The protection of the environment, now and as a duty towards the humanity that is still to come, belongs to the origins of bioethical discourse, and is enriched by the contribution that comes from the intergenerational theory of law and the Constitution. The attention to the future (in terms of responsibilities and duties towards future generations or even of one’s rights) is one of the most fascinating and complicated topics of modern constitutionalism, and a real challenge for the traditional categories of politics and democracy.
Keywords: Bioethics; sustainability; future generations; Constitution; environment